Using radar‐derived parameters to forecast lightning cessation for nonisolated storms. Issue 6 (21st March 2017) - Davey, Matthew J.; Fuelberg, Henry E.
Abstract: Lightning impacts operations at the Kennedy Space Center (KSC) and other outdoor venues leading to injuries, inconvenience, and detrimental economic impacts. This research focuses on cases of "nonisolated" lightning which we define as one cell whose flashes have ceased although it is still embedded in weak composite reflectivity ( Z ≥ 15 dBZ) with another cell that is still producing flashes. The objective is to determine if any radar‐derived parameters provide useful information about the occurrence of lightning cessation in remnant storms. The data set consists of 50 warm season (May–September) nonisolated storms near KSC during 2013. The research utilizes the National Lightning Detection Network, the second generation Lightning Detection and Ranging network, and polarized radar data. These data are merged and analyzed using the Warning Decision Support System‐Integrated Information at 1 min intervals. Our approach only considers 62 parameters, most of which are related to the noninductive charging mechanism. They included the presence of graupel at various thermal altitudes, maximum reflectivity of the decaying storm at thermal altitudes, maximum connecting composite reflectivity between the decaying cell and active cell, minutes since the previous flash, and several others. Results showed that none of the parameters reliably indicated lightning cessation for even our restrictive definition of nonisolated storms. Additional research is needed before cessation can be determined operationally with the high degree of accuracy required for safety. Key Points: Radar‐derived parameters are investigated as guidance whether lightning cessation has occurred Parameters showing most promise are graupel at ‐10 degrees celsius and ‐15 degrees celsius, and maximum composite reflectivity >35 dBZ at ‐10 degrees celsius and >40 dBZ at ‐5 degrees celsius. No schemes produce zero false alarms